Local axonal translation: regulation of neuronal polarity, axon development and survival - Lucci, Cristiano (2020)
Both the establishment of neuronal polarity and axonal growth are critical steps in the development of the nervous system, allowing neurons to fulfil their functional role, transmitting and receiving electrical signals. The local translation of mRNAs in the axon provides fine regulation of protein expression, and is now known to participate in axon development, homeostasis and degeneration. In this context, microRNAs play a fundamental role in the spatiotemporal regulation of axonal translation and, by doing so, can regulate almost every aspect nervous system development, physiology and disease. This thesis focuses on elucidating the mechanisms by which local protein translation in the axon can regulates axon development and survival. I show how axonal protein synthesis contributes in supplying the needs of the axon and maintaining its homeostasis. Repression of protein translation restricted to the axonal compartment of microfluidic chambers triggers axon degeneration in mouse sensory neurons. Moreover, I identified four microRNAs as potential candidate regulators of axon degeneration pathways. I then investigated the role of a single microRNA, miR-26a, in early stage primary cortical neuron development. I show that miR-26a is highly expressed in neuronal cultures and regulates both neuronal polarity and axon growth. Specifically, inhibition of miR-26a reduces the number of polarised neurons, whilst its over-expression produces the opposite phenotype and increases the number of neurons with multiple axon-like processes via the targeting of GSK3β. Using compartmentalised microfluidic neuronal cultures, I also identified a local role for miR-26a in the axon, where the repression of local synthesis of GSK3β controls axon development and growth. Removal of this repression in the axon triggers local translation of GSK3β protein and subsequent transport to the soma, where it can impact axonal growth mechanism. These results demonstrate how the axonal miR-26a can regulate local protein translation in the axon to facilitate retrograde communication to the soma and amplify neuronal responses, in a mechanism that influences axon development.